Thermal Performance of Edible Vertical Greenery System In High-rise Residential Balcony - Basher, Hazril Sherney (International Journal of Integrated Engineering, 2019)
The vertical greenery system (VGS) is a passive solution for urban greening in multi-storey buildings. This system could prove to be beneficial towards the building occupants. It is designed to provide urban greening for the benefits of environmental, economic and social aspects. As cities are experiencing urban heat island due to excessive development and overpopulation, the vertical greenery system is introduced to counter this issue. This paper presents a series of measured data from the use of balcony space at Putra Place Condominium, Penang. Apart from that, this paper also uses Psophocarpus Tetrogonobulus (Winged Bean Plant) as the core plant for VGS. It is chosen based on the ability to provide vegetable pod, have longer lifespan and withstand heat gain from long sun exposure at high-rise condition. The VGS that has been installed managed to reduce the indoor dry bulb temperature (DBT) and mean radiant temperature (MRT) by an average of 0.94°C and 1.25°C. The overall finding from this experiment confirms that when exposed to higher outdoor temperatures facing the west orientation, the indoor DBT and MRT behind the VGS managed to be stabilised and maintained at a constant 30.6°C. Thus, reducing the needs for future building energy cooling load.